To solve the equation, we need to isolate the variable x.
2/3(x - 6) = 14
To remove the fraction, let's multiply both sides of the equation by the reciprocal of 2/3, which is 3/2, or simply 1.5.
1.5 * 2/3(x - 6) = 1.5 * 14
Multiplying:
1.5 * 2/3(x - 6) = 21
1.5(x - 6) = 21
Distribute 1.5:
1.5x - 9 = 21
Add 9 to both sides:
1.5x - 9 + 9 = 21 + 9
1.5x = 30
Divide both sides by 1.5:
(1.5x)/1.5 = 30/1.5
x ≈ 20
Therefore, the solution to the equation is x ≈ 20.
Solve 2/3(x -6) = 14
3 answers
The options are:
A. -15
B. 27
C. -27
D. 15
A. -15
B. 27
C. -27
D. 15
To solve the equation 2/3(x - 6) = 14, we need to isolate the variable x.
First, let's multiply both sides of the equation by 3/2 to remove the fraction:
(3/2)(2/3)(x - 6) = (3/2)(14)
Simplifying:
(x - 6) = 21
Next, add 6 to both sides to isolate x:
(x - 6) + 6 = 21 + 6
x = 27
Therefore, the solution to the equation is x = 27.
The correct option is B. 27.
First, let's multiply both sides of the equation by 3/2 to remove the fraction:
(3/2)(2/3)(x - 6) = (3/2)(14)
Simplifying:
(x - 6) = 21
Next, add 6 to both sides to isolate x:
(x - 6) + 6 = 21 + 6
x = 27
Therefore, the solution to the equation is x = 27.
The correct option is B. 27.